A VLSI Implementation of a New Low Voltage 5th Order Differential Gm-C Low-Pass Filter with Auto-Tuning Loop in CMOS Technology - BOZOMITU, R. G.; COJAN, N. (Advances in Electrical and Computer Engineering, 2011)
In this paper a new low voltage 5th order Gm-C Bessel type low-pass filter (LPF) with auto-tuning loop and higher dynamic range, designed in CMOS technology, is presented. The cut-off frequency can be tuned in (10-42)MHz range by modifying the values of the grounded capacitors using a digital logic. The proposed structure is based on an auto-tuning loop in order to maintain the Gm/C ratio independent of the process, supply voltage and temperature variations, assuring the cut-off frequency of the LPF independently of these factors. The proposed 5th order Gm-C Bessel type low-pass filter provides 5% variation of the cut-off frequency in all critical corners, a 400mVpp(diff) dynamic range, THD less than 1% and 21.6mW power consumption from 1.8V supply voltage. The simulations performed in 65nm CMOS process confirm the theoretical results.